The transition from acute to persistent pain: the identification of distinct trajectories among women presenting to an emergency department. Issue 11 (November 2020) - Burns, John W.; Janssen, Imke; Lillis, Teresa; Mulcahy, Morgan; Purim-Shem-Tov, Yanina A.; Bruehl, Stephen; Burgess, Helen J.; Fischer, Alexandra; Rim, Katie; Aranda, Frances; Pinkerton, Linzy; Hobfoll, Stevan
Abstract : Abstract: Posttraumatic stress disorder (PTSD) symptoms and other negative psychosocial factors have been implicated in the transition from acute to persistent pain. Women (N = 375) who presented to an inner-city emergency department (ED) with complaints of acute pain were followed up for 3 months. They completed a comprehensive battery of questionnaires at an initial visit and provided ratings of pain intensity at the site of pain presented in the ED during 3 monthly phone calls. Latent class growth analyses were used to detect possible trajectories of change in pain intensity from the initial visit to 3 months later. A 3-trajectory solution was found, which identified 3 groups of participants. One group (early recovery; n = 93) had recovered to virtually no pain by the initial visit, whereas a second group (delayed recovery; n = 120) recovered to no pain only after 1 month. A third group (no recovery; n = 162) still reported elevated pain at 3 months after the ED visit. The no recovery group reported significantly greater PTSD symptoms, anger, sleep disturbance, and lower social support at the initial visit than both the early recovery and delayed recovery groups. Results suggest that women with high levels of PTSD symptoms, anger, sleep disturbance, and low social support who experience an acute pain episode serious enough to prompt an ED visit may maintain elevated pain at this pain site for at least 3 months. Such an array of factors may place women at an increased risk of developing persistent pain following acute pain. Abstract : Women with high levels of posttraumatic stress disorder symptoms, anger, poor sleep, and low social support who experience acute pain may maintain elevated pain for 3 months.